A New Evolutionary Algorithm Based on Bacterial Evolution and Its Application for Scheduling A Flexible Manufacturing System - Chandramouli Anandaraman; Arun Vikram Madurai Sankar; Ramaraj Natarajan (Institute of Research and Community Outreach - Petra Christian University, 2012)
A new evolutionary computation algorithm, Superbug algorithm, which simulates evolution of bacteria in a culture, is proposed. The algorithm is developed for solving large scale optimization problems such as scheduling, transportation and assignment problems. In this work, the algorithm optimizes machine schedules in a Flexible Manufacturing System (FMS) by minimizing makespan. The FMS comprises of four machines and two identical Automated Guided Vehicles (AGVs). AGVs are used for carrying jobs between the Load/Unload (L/U) station and the machines. Experimental results indicate the efficiency of the proposed algorithm in its optimization performance in scheduling is noticeably superior to other evolutionary algorithms when compared to the best results reported in the literature for FMS Scheduling.